Improvement of paintball robot [electronic resource] - 639433 Mohamad Faiz Abdull Aziz, 1992- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014